ENVIRONMENTAL POLLUTION RESULTING FROM BRICK FACTORIES AND THE ROLE OF ENVIRONMENTAL TAX IN REDUCING IT - Haider Omran seher; Ali Murad Khudadad; Ibtisam Jebur Wannas Alhweesah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The phenomenon of environmental pollution resulting from the smoke of brick factories is one of the most dangerous phenomena facing the environment in Iraq in general, and there are data indicating a large and increasing exceeding the levels of toxic gases polluting the environment resulting from the smoke of brick factories according to the permissible global and local environmental determinants, which threatens the existence of a danger. A great deal of environmental disaster in the future if the situation continues as it is now. Therefore, the research included a problem that the Iraqi airspace suffers from the dangerous effects of environmental pollution resulting from the smoke of brick factories, and that suffering is exacerbated by the increasing need for the state to continue and expand these activities and the associated great and dangerous environmental damage. In light of the absence of environmental taxes within the structure of the tax system in Iraq, the matter requires state intervention to reduce the phenomenon of environmental pollution by imposing environmental taxes on brick factories, with the aim of protecting society and the environment from the dangers of that.